PLACE OF FIRST TRIMESTER ULTRASOUND AT THE UNIVERSITY TEACHING HOSPITAL OF BOGODOGO (UTH-B) IN BURKINA FASO - Adama Ouattara (Andalas Obstetrics And Gynecology Journal, 2024)
AbstractObjective: To describe the experience of the UTH-Bogodogo obstetrics and gynecology department in ultrasound determination of fetal sex in the first trimester of pregnancy.Patients and methods: This was a prospective descriptive study conducted over a 30-month period from February 1, 2021 to June 30, 2022 in the gynecological and obstetric ultrasound unit of the UTH-Bogodogo in Ouagadougou. The study sample consisted of 311 fetuses. The sample included all pregnant women who came for an obstetrical ultrasound scan in a non-emergency situation, whose gestational age was between the 11th and 14th week of amenorrhea, and who expressed a wish to know the fetal sex. The methods described by Mazza and Efrat were used to determine fetal sex. Patients were followed until delivery, after clinical verification of the sex of their newborns. Data were collected using an individual data collection form. Participation in the study was conditional on patients signing an informed consent form.Results: Fetal sex determination was possible in 280 of 311 fetuses, for a feasibility rate of 89.7%. In the remaining 31 cases, it was not possible to determine the fetal sex, as the position of the fetus did not allow a clear view of the genital bud. In terms of reliability, of the 238 fetuses monitored, fetal sex determination was correct in 204 fetuses, for a success rate of 85.7%. Accuracy was better when sex determination was performed after 12 weeks of amenorrhea. There was no significant difference in measurements between single and multiple fetuses.Conclusion: ultrasound determination of fetal sex at first birth could be an effective, simple, available and inexpensive option in developing countries.